Influence of Immediate Coronal Restoration Placement on Microhardness of CEM Cement: An In Vitro Study - Kazemipoor, Maryam; Tamizi, Maedeh (Iranian Endodontic Journal, 2018)
Introduction: Coronal restoration could affect the setting reaction of the underlying CEM cement. The aim of the present study was to evaluate the effect of immediate coronal restoration placement on the subsurface microhardness of CEM cement. Methods and Materials: In 50 extracted human mandibular molars, access cavities were prepared and CEM cement was placed in the pulp chamber at a 3-mm thickness. Samples were divided into ten groups (n=5). CEM cement was placed and after 10 min, two groups were restored with Zonalin temporary restoration and eight groups were restored with glass ionomer cement (GIC), resin modified glass ionomer (RMGI), resin based composite and amalgam respectively. Vickers microhardness number (VHN) of CEM cement was measured in two time intervals (7- and 21-days). Data was analyzed with SPSS and two-way analysis of variance and Bonferroni tests. Level of significance was set at the 5%. Results: The mean VHN of CEM cement showed statistically significant differences only between Zonalin and amalgam groups (P=0.021). There were also significant differences considering the effect of time (P=0.042) and material (P=0.046). Although the effect of time-material on the microhardness values showed no statistically significant differences (P=0.636). Conclusion: Based on the results of the present study, immediate placement of final restorations affects the setting reaction in underlying CEM cement. Therefore, sufficient moist curing and hydration should be guaranteed before the placement of the coronal restoration. Keywords: Calcium-enriched Mixture; CEM Cement; Dental Restoration; Setting Time; Vickers Microhardness